2017
DOI: 10.1242/bio.021618
|View full text |Cite
|
Sign up to set email alerts
|

Novel immunodeficient Pde6b rd1 mouse model of retinitis pigmentosa to investigate potential therapeutics and pathogenesis of retinal degeneration

Abstract: Retinitis pigmentosa (RP) is a common retinal degeneration disease caused by mutation in any gene of the photo transduction cascade and results in photoreceptor dystrophy. Over decades, several animal models have been used to address the need for the elucidation of effective therapeutics and factors regulating retinal degeneration to prohibit or renew the damaged retina. However, controversies over the immune privilege of retina during cell transplantation and the role of immune modulation during RP still rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 47 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…Transplantation of RNLCs in immune compromised NOD.SCID-rd1 mice via trans-corneal sub-retinal transplantation resulted in their engraftment owing to proximity between damaged layer and site of transplanted cells [ 2 ] and that it is more immune privileged than other retinal regions [ 46 ]. As previously shown in our lab and by other groups, the cell engraftment efficiency in an immune-deficient rd1 model is higher than an immune-competent rd1 model [ 20 , 47 , 48 ]. Therefore, we performed cell transplantation studies on immunodeficient rd1 mouse model to assess cell integration.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Transplantation of RNLCs in immune compromised NOD.SCID-rd1 mice via trans-corneal sub-retinal transplantation resulted in their engraftment owing to proximity between damaged layer and site of transplanted cells [ 2 ] and that it is more immune privileged than other retinal regions [ 46 ]. As previously shown in our lab and by other groups, the cell engraftment efficiency in an immune-deficient rd1 model is higher than an immune-competent rd1 model [ 20 , 47 , 48 ]. Therefore, we performed cell transplantation studies on immunodeficient rd1 mouse model to assess cell integration.…”
Section: Discussionsupporting
confidence: 67%
“…All the mice required during different experiments (NOD.CB17-Prkdcscid/J (NOD SCID), CBA/J and BALB/cByJ (BALB/c) were procured from the Jackson Laboratory, USA while the NOD-SCID-rd1 mouse model was developed in-house as reported previously [ 20 ]. The animals received ad libitum access to acidified autoclaved water and food.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first characterized the degeneration phenotype in these rd mice with NOG background because immune responses have been suggested to accompany or modulate the pathogenesis of neurodegenerative diseases ( Cuenca et al., 2014 , González et al., 2014 , Jin et al., 2016 , Noailles et al., 2016 , Yoshida et al., 2013a , Yoshida et al., 2013b , Zabel et al., 2016 , Zeng et al., 2005 , Zhao et al., 2015 ). Rd1 mice in the background of SCID, or in combination with RAG-1 knockout (no functional B and T cells) or a C1qα knockout (no functional classical complement activation pathway) ( Rohrer et al., 2007 ) or NOD (no functional B and T cells and low activity of NK cells) ( Mishra et al., 2017 ) showed no difference in the degeneration speed, while rd10 mice with Ccr2 knockout ( Guo et al., 2012 ) and Cx3cr1 knockout ( Peng et al., 2014 ) exhibited slower degeneration. We next transplanted hESC retinal sheets, to confirm the long-term survival and functional integration of graft cells in NOG- rd1-2J mice by immunohistochemistry and electrophysiology recording.…”
Section: Introductionmentioning
confidence: 99%
“…Rohrer et al crossed rd1 mice with Scid or Rag1 −/− mice, both of which lack functional T and B lymphocytes, and showed that the deficiency of lymphocytes did not change rod cell death (145). In another study, Mishra et al demonstrated that rod degeneration was mildly attenuated in rd1 Nod.Scid mice, which are deficient in T, B, and NK cells (146). These findings suggest that NK cells may play a minor role in rod cell death in RP, whereas lymphocytes may not have a significant function, at least solely by themselves.…”
Section: Functional Roles Of Inflammatory Response In Cone Cell Deathmentioning
confidence: 88%